2019
DOI: 10.13189/ujer.2019.071112
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effectiveness of Polish and Ukrainian Basic Training Programs in Physical Education for 9-10-year-old Pupils

Abstract: The article examines the influence of physical education classes conducted on the basis of Polish and Ukrainian basic training programs on the level of physical fitness and physical development of pupils in secondary schools aged 9-10 years. The main features of the Polish and Ukrainian basic training programs are revealed, a comparative analysis of the advantages and disadvantages of each program has been performed. The study involved 132 pupils of 4 forms of three schools in Khmelnytskyi (Ukraine), who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
5
16
0
Order By: Relevance
“…At the same time, the system of the physical education of students who have chronic diseases, health problems, con-genital anomalies and the low levels of physical development and physical fitness, do not completely solves the problem of the restoration of working capacity and ensuring the normal functioning [7,8,9,10,11]. One of the causes of the disease incidence and health problems of students of Ukraine is the unsatisfactory condition of the physical education system at schools and higher educational establishments and its obsolescence [12,13,14,15,16]. If one summarizes the essence of the shortcomings in the system of physical education of the students of special medical groups, suggestions, and requirements of teachers regarding its reformation, it becomes clear that one can find the necessary ways to solve this problem by modernizing the system of physical education.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the system of the physical education of students who have chronic diseases, health problems, con-genital anomalies and the low levels of physical development and physical fitness, do not completely solves the problem of the restoration of working capacity and ensuring the normal functioning [7,8,9,10,11]. One of the causes of the disease incidence and health problems of students of Ukraine is the unsatisfactory condition of the physical education system at schools and higher educational establishments and its obsolescence [12,13,14,15,16]. If one summarizes the essence of the shortcomings in the system of physical education of the students of special medical groups, suggestions, and requirements of teachers regarding its reformation, it becomes clear that one can find the necessary ways to solve this problem by modernizing the system of physical education.…”
Section: Introductionmentioning
confidence: 99%
“…The scholars [29,30] note that the level of students' health depends significantly on the state of physical education at school, following a healthy lifestyle by school pupils, and the prevention of diseases among pupils, that is, on the initial level of health of a HEI applicant. There has been a significant deterioration of health and a decrease in the level of fitness of young students in Ukraine for many years [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The studies of many scientists [21,27] showed that in the developed countries, the issues of physical education and mass sports among students are of great importance, considering them as the most cost-effective and efficient means of preventing diseases, strengthening the gene pool and solving a number of other social problems. Thus, analyzing the experience of the physical improvement process organization at HEI in Poland, Yu.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of research, aimed at solving the problems of physical education of students [20,21,22], showed that the organization of physical education of students on the basis of their division into groups by interests in sports increases motivation for classes, affects the regularity of their attendance, promotes their health, and increases their physical fitness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation